Fundamental study on the circular polarization antenna for RFID UHF reader - Ariff, M. H.; Ibrahim, Mohd Zamri; Khatun, Sabira (2019)
A few years after the early investigation on ultra-high frequency (UHF) wireless system, considerable research efforts have been put into the design of UHF antennas for radio frequency identification systems. These UHF antennas are essential for providing wireless communications based on the use of very narrow pulses on the order of nanoseconds, covering a small bandwidth in the frequency domain, and over very short distances at very low power densities. In this project, new models of rectangular, T slotted and angular slot UHF antennas are proposed by studying their parameters of antennas such as return loss, gain, radiation pattern and voltage standing wave ratio. The wideband behavior is due to the fact that the currents along the edges of the slots introduce an additional resonance, which, in conjunction with the resonance of the main patch, produce an overall frequency response characteristic. These antennas are considerable small than others listed in the references, which their sizes are less than a wavelength, compact, and suitable for many RFID applications. The configuration of slots type for both patches and pin feed are considered as a novelty and contribution in this project. The geometry of the antenna implies the current courses and makes it possible to identify active and neutral zones in the antenna, thus it will be possible to fix which elements will act on each characteristic. This project also investigated the ability of slotted UHF antennas to improved read range and gain between tags and UHF RFID Reader within the same field test environment. Inserting a half-wavelength slot structure with additional small patches gap attached have resulted frequency notched band characteristics. The measured return loss, radiation patterns, and phase agree well with the simulated results. The antenna provides a directional pattern with the return loss less than -10 dB and circular in phase.